Potencial probiótico de Lactobacillus crispatus isolados do ecossistema vaginal de mulheres saudáveis em menacme - Karine Cachoeira Rodrigues (2012)
Lactobacilli are usually the most prevalent microorganisms on vaginal fluid of healthy women in menacme. These microorganisms play an important role on the local ecosystem as they protect the mucosa against the pathogens, including those associated with bacterial vaginosis(BV), which is the most common vaginitis among women of reproductive age. That happens mainly due to the lactobacilli ability to adhere to vaginal epithelial cells and also due to pathogens growth inhibition. It seems incontestable that the disruption of the microbial balance is the basis of this complex disease. Therefore the treatment should be based on correcting the dysbiosis without a negative impact on the resident microbiota lactobacilli. The existence of studies that investigate the best alternative to treat this infection is a consequence of the low cure rates and the high levels of recurrence reported by the currently recommendedtreatments. Most of the studies that have evaluated the lactobacilli as probiotics used mischaracterized samples that do not have the necessary properties for this purpose. The present work investigated the in vitro and in vivo probiotic properties of two Lactobacillus crispatus samples isolated from the vaginal ecosystem of healthy women in menacme, since it is often the predominant specie in this microenvironment. The in vivo tests were carried out with sample L.04 because it showed a better antagonist substance production, cellular surface hydrophobicity and susceptibility to the evaluated antibiotics. The use of BV murine model in conventional mice revealed a protection against the Gardnerella vaginalis ATCC® 14018 experimental infection, which was evidenced by the reduction in histhopatological lesions caused by this bacterium.